(untitled) (Revista da Faculdade de Medicina Veterinária, Universidade de São Paulo, 1946)
This paper includes two parts: mainly the A. A. review not only a summary of the modifications that have occurred in the technic of the kypophysation of fishes in Brazil, from the early works of VON IHERING as they also appoint alls the advantages brought to the Brazilian pisciculture by the utilization of the method above referred; secondly the A.A. appoint the recent modifications in the original process by the use of a glycerinate extract from fish hypophysis (Fonseca Ribeiro and Tabarelli Neto). To such innovation they have collaborated according to papers previously published, in which they demonstrated its efficacy. They founded experimentally new behaviors of glycerinate extract, especially referring to the capacity of the conservation of its hormonal activity even when kept in the icebox or in the room temperature. They describe the advantages off erred, by the modifications mentioned as well as some results obtained by other workers who have used the glycerinate extract.